Morphometric study of the anatomic relationship between large retroperitoneal blood vessels and intervertebral discs of the distal segment of the lumbar spine: a clinical significance - Hakija Bečulić; Igor Sladojević; Aldin Jusić; Rasim Skomorac; Melica Imamović; Alma Efendić (Medicinski glasnik, 2019)
Aim: To analyse potential clinical implications of the distance between large retroperitoneal vessels and lower segment of the lumbar spine in the supine and prone position. Methods: Prospective, non-randomised study included 40 patients of different age and gender. For all patients magnetic resonance imaging of the lumbar spine was performed in supine and prone position. The level of aortal bifurcation, common iliac vein confluence, the distance from the anterior and posterior aspect of the annulus to the posterior wall of the large retroperitoneal vessels were analysed. Results: The study included 40 patients, 22 (55%) males and 18 (45%) females. The level of aortal bifurcation was higher in prone compared to supine position (χ2 = 29.88571; p˂0.05). In supine and prone positions, the common iliac veins confluence was most commonly at the level of the lower third of the L4 vertebra (p˃0.05). There was a statistically significant difference between the distance from the left common iliac artery to the anterior contour of L4/L5 intervertebral disc (p˂0.05). Conclusion: Knowledge of the anatomic relationship between iliac vessels and structures of the lower segment of the lumbar spine is very important in the prevention of a potentially severe complication, such as artificial common iliac vessels rupture. Our study showed that the risk of lesions of the common left iliac artery was lesser in the prone position.
Keywords: iliac artery; iliac vein; magnetic resonance imaging; prone position; supine position